2015
DOI: 10.3390/ijms161126031
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine Induces Apoptosis and Inhibits Migration of HCT-116 Human Colorectal Cancer Cells

Abstract: Evodiamine (EVO) exhibits strong anti-cancer effects. However, the effect of EVO on the human colorectal cancer cell line HCT-116 has not been explored in detail, and its underlying molecular mechanisms remain unknown. In the present study, cell viability was assessed by Cell Counting Kit-8 (CCK-8). Cell cycle and apoptosis were measured by flow cytometry, and morphological changes in the nucleus were examined by fluorescence microscopy and Hoechst staining. Cell motility was detected by Transwell assay. ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…However, based on our present data showing that z-DEVD-fmk completely blocked the apoptotic cell death induced by EEER, we suggest that the role of AIF and endoG in EEERinduced apoptosis might be slight. Notably, several preceding studies have also reported that evodiamine, an alkaloid isolated from E. rutaecarpa, induced mitochondria-mediated apoptosis in several cancer cell lines (20)(21)(22)(23)(24)(25)(26), which supports our current results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, based on our present data showing that z-DEVD-fmk completely blocked the apoptotic cell death induced by EEER, we suggest that the role of AIF and endoG in EEERinduced apoptosis might be slight. Notably, several preceding studies have also reported that evodiamine, an alkaloid isolated from E. rutaecarpa, induced mitochondria-mediated apoptosis in several cancer cell lines (20)(21)(22)(23)(24)(25)(26), which supports our current results.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, there have been other reports indicating that inhibition of the activity of the mechanistic target of rapamycin (mTOR) signal systems, or insulin-like growth factor 1, is involved in apoptosis of human cancer cells exposed to evodiamine (22,23). Furthermore, it has been reported that the inhibition of human cancer cell proliferation by evodiamine is associated with overcoming of multidrug resistance related to nuclear factor-kappa B signaling pathway inhibition and inhibition of invasive activity by calcium/JNK signaling-mediated autophagy induction and to increases in the activity of matrix metalloproteinase (24)(25)(26) However, to date no systematic study has been conducted on E. rutaecarpa extracts per se. In the current study, we explored the anti-cancer effects of the ethanol extract of E. rutaecarpa immature fruits (EEER) in HeLa human cervical cancer cells and investigated the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Evodiamine induced cell-cycle arrest at G 2 /M phase in human UCC cells was firstly observed in our study (Figure 3). It also reported in various cancers post-treatment with evodiamine including human leukemic T-lymphocytes, prostate cancer, cervix carcinoma, thyroid cancer, colorectal cancer, ovarian cancer, and lung cancer (10,11,14,15,22,(34)(35)(36)(37)(38). In addition, we and others have demonstrated apoptosis in human UCC and other cancers after evodiamine treatment.…”
Section: Discussionsupporting
confidence: 69%
“…EVO displays antimigratory, anti-invasive, and antimetastatic activity in human lung cancer, breast cancer, and nasopharyngeal cancer cells in vitro and in mouse models. EVO exerts antimetastatic activity by multiple mechanisms, such as regulation of matrix metalloproteinase-3 activity, p38 kinase activity, extracellular signal-regulated kinase activity, and Janus kinase/STAT pathway, and downregulation of phosphoglucose isomerase (Du et al, 2013;Peng et al, 2015;Zhao et al, 2015).…”
Section: Antineoplastic Activity Of Natural Capsaicin Analogsmentioning
confidence: 99%